Cancer stem cells in radiation response: current views and future perspectives in radiation oncology. (3rd July 2019) - Peitzsch, Claudia; Kurth, Ina; Ebert, Nadja; Dubrovska, Anna; Baumann, Michael
Abstract: Purpose: Despite technological improvement and advances in biology-driven patient stratification, many patients still fail radiotherapy resulting in loco-regional and distant recurrence. Tumor heterogeneity remains a key challenge to effective cancer treatment, and reliable stratification of cancer patients for prediction of outcomes is highly important. Intratumoral heterogeneity is manifested at the different levels, including different tumorigenic properties of cancer cells. Since John Dick et al. isolated leukemia initiating cells in 1990, the populations of tumor initiating or cancer stem cells (CSCs) were identified and characterized also for a broad spectrum of solid tumor types. The properties of CSCs are of considerable clinical relevance: CSCs have self-renewal and tumor initiating potential, and the metastases are initiated by the CSC clones with the ability to disseminate from the primary tumor site. Conclusion: Evidence from both, experimental and clinical studies demonstrates that the probability of achieving local tumor control by radiation therapy depends on the complete eradication of CSC populations. The number, properties and molecular signature of CSCs are highly predictive for clinical outcome of radiotherapy, whereas targeted therapies against CSCs combined with conventional treatment are expected to provide an improved clinical response and prevent tumor relapse. In this review, we discuss the modern methods to study CSCs in radiation biology, the role of CSCs in personalized cancer therapy as well as future directions for CSC research in translational radiooncology.